Accelerating the Jordanian Energy Transition - Weko, Silvia; Hermann, Judith; Apergi, Maria; Eicke, Laima; Goldthau, Andreas; Kurniawan, Jude; Schuch, Esther (2022)

Breaking the carbon lock-in: Identifying pathways for Malaysia towards a low-carbon future - Schuch, Esther; Apergi, Maria; Yik Kuen Chow, Deborah; Eicke, Laima; Goldthau, Andreas; Kurniawan, Jude; Lima-de-Oliveira, Renato; Gen Tan, Zhai; Weko, Silvia (Technological Forecasting and Social Change, 2024)
Keywords: Emerging economies; Energy transition; Carbon lock-in; CIB; Scenarios

Bridging the low-carbon technology gap? Assessing energy initiatives for the Global South - Weko, Silvia; Goldthau, Andreas (Energy Policy, 2022)
Keywords: SDG 7; Technology transfer; Intellectual property rights; Renewable energy; Public-private partnerships

Climate Technology Diffusion and Transfer in the International Trade System - Weko, Silvia; Goldthau, Andreas; Quitzow, Rainer (Remaking the Global Trading System for a Sustainable Future Project (Yale, Tufts, SRC), 2023)

Communitarians, cosmopolitans, and climate change: why identity matters for EU climate and energy policy - Weko, Silvia (Journal of European public policy, 2022)
Keywords: Attitudes; energy policy; climate policy; social cleavages; political cleavages

Countering the risk of an uneven low-carbon energy transition - Eicke, Laima; Weko, Silvia; Goldthau, Andreas (2019)

Covid-19 and Carbon Lock-In: Impacts on the Energy Transition - Weko, Silvia; Eicke, Laima; Quitzow, Rainer; Bersalli, Germán; Lira, Flavio; Marian, Adela; Süsser, Diana; Thapar, Sapan; Xue, Bing (2020)

Creating a climate-just Carbon Border Adjustment Mechanism: Considering impacts on third countries in the scheme’s evaluation - Hermann, Judith; Weko, Silvia; Apergi, Maria; Eicke, Laima; Marian, Adela (2023)

Datasets and time series for energy policy research and modelling - Chaianong, Aksornchan; Hoffart, Franziska M.; Kerker, Nina; Lilliestam, Johan; Weko, Silvia (1. NFDI4Energy Conference 2024, 2024)
To reach the Paris Agreement’s goal to limit global warming to 1.5°C, a crucial system-wide transformation, and relevant public policies are required to push toward a sustainable, innova- tive, and inclusive future for different sectors, including the energy sector [1]. Interdisciplinary energy models have become essential tools to support the policy-making process of the low- carbon transition, as discussed in [2], [3]. However, most empirical analyses rarely focus on integrating social and political factors into their studies. Moreover, published open-access en- ergy policy research datasets are scarce or not in machine-readable formats [4]. As a result, we aim to develop practices for collecting datasets for energy policy-related research that could support more efficient research in the field and enable the quantitative analysis of energy pol- icy/social and political factors into energy modelli

Does green growth foster green policies? Value chain upgrading and feedback mechanisms on renewable energy policies - Eicke, Laima; Weko, Silvia (Energy Policy, 2022)
Keywords: Renewable energy; Value chain; Policy feedback theory; Public policy; Innovation; Energy transition

Fostering a Sustainable and Secure Energy Supply for Kenya - Apergi, Maria; Hermann, Judith; Eicke, Laima; Goldthau, Andreas; Kurniawan, Jude; Schuch, Esther; Weko, Silvia (2022)

Fostering Energy Transitions in the Global South: Insights from Chile, Jordan, Malaysia, and Kenya - Hermann, Judith; Apergi, Maria; Eicke, Laima; Goldthau, Andreas; Schuch, Esther; Weko, Silvia (2022)

Is clean technology transfer an empty promise? - Weko, Silvia (2024)

Is renewable energy technology trade more or less conflictive than other trade? - Apergi, Maria; Zimmermann, Eva; Weko, Silvia; Lilliestam, Johan (Energy Policy, 2023)
Renewable energy changes the geopolitics of energy: whereas access to fossil fuel resources were key in the past, control over technology and industry will be key in the future. Consequently, different scholars have predicted that a growing focus on renewables will increase or decrease conflict in the energy sector, with no consensus on which is most likely. Here, we investigate the degree of conflict in renewable energy technology (RET) trade by analyzing data on 7041 trade conflicts 1995–2020, guided by two sets of theory-driven hypotheses. We show that RET trade is associated with more, longer, and more intense trade conflicts than other trade conflicts for 1995–2016. This supports the neorealist, geo-economic view of countries being willing to risk conflict to increase their share of a market rather than avoiding conflicts to increase the overall market size. It also contradicts the view that renewables will reduce conflict: at least in the past and regarding trade, it has increased rather than decreased conflict. For 2017–2020, this trend is reversed and RET trade became significantly less conflictive than other trade. Our findings imply that improved conflict-resolution institutions for RET are needed. We also suggest establishing specific institutions to govern trade in immature technologies.
CRIS-Team Scopus Importer:2023-06-14
Keywords: Energy transition; Geo-economics; International relations; Renewable energy technology; Trade conflicts; World trade organization

New Sites of Accumulation? Why Intangible Assets Matter for Energy Transitions - Weko, Silvia (Review of Political Economy, 2024)
Keywords: big tech; Global value chains; Energy transition; Intellectual monopoly

Pathways to a sustainable electricity sector in Kenya: Challenges and transformational factors - Apergi, Maria; Eicke, Laima; Goldthau, Andreas; Kurniawan, Jude; Schuch, Esther; Weko, Silvia (Utilities Policy, 2024)
Keywords: Energy scenarios; Kenya; Cross-impact balance analysis

Phasing-out Big Oil, Phasing-in Big Tech? The importance of data and AI for the energy transition - Weko, Silvia (2024)

Pulling up the carbon ladder? Decarbonization, dependence, and third-country risks from the European carbon border adjustment mechanism - Eicke, Laima; Weko, Silvia; Apergi, Maria; Marian, Adela (Energy Research & Social Science, 2021)
Keywords: European Green Deal; Global South; CBAM; EU; MRV; Carbon leakage; Border carbon adjustment

Resource exporter or R&D champion? Leverage points and transition pathways for the Chilean energy sector - Eicke, Laima; Apergi, Maria; Goldthau, Andreas; Kurniawan, Jude; Schuch, Esther; Weko, Silvia (Energy for Sustainable Development, 2023)
Keywords: Energy transition; Innovation; Energy policy; Technology; Value chains; Political economy; Scenario

Stakeholder-based scenario building: How does it work in practice? - Hermann, Judith; Apergi, Maria; Goldthau, Andreas; Weko, Silvia; Schuch, Esther; Eicke, Laima; Kurniawan, Jude (2022)

The global energy transition and the global south - Goldthau, Andreas; Eicke, Laima; Weko, Silvia (The Geopolitics of the Global Energy Transition, 2020)

The Global Impacts of an EU Carbon Border Adjustment Mechanism - Weko, Silvia; Eicke, Laima; Marian, Adela; Apergi, Maria (2020)

The Politics of Green Hydrogen Cooperation: Emerging Dynamics in Morocco, Algeria, and Mauritania - Weko, Silvia; Farrand, Andrew; Fakoussa, Dina; Quitzow, Rainer (2023)
Europe's growing interest in securing green hydrogen from North Africa is part of a strategic effort to enhance its energy security. The promise of green hydrogen projects in Morocco, Algeria, and Mauritania is substantial, offering economic growth and job opportunities. However, numerous factors limit these countries’ ability to develop robust local green hydrogen sectors, while political disputes—particularly around Western Sahara—complicate regional collaboration. European actors can play an important role in advancing green hydrogen’s development in the region, but must tread carefully to secure local buy-in and avoid exacerbating tensions within or between these countrie

The UK Hydrogen Strategy: Falling Behind in the Green Race? - Weko, Silvia (2023)
The UK aims to become a leader in green industries by developing a competitive hydrogen industry, bringing new jobs, and revitalizing peripheral areas of the country. Hydrogen is also seen as an opportunity for the country to improve its energy security, as extracting fossil fuels is increasingly costly and unfeasible given the UK’s decarbonization goals. Its hydrogen strategy takes a “twin track” approach, that is, simultaneously promoting hydrogen from gas with carbon capture and hydrogen from low-carbon electricity. The UK strategy focuses on the importance of applying hydrogen to industry including chemicals, steel, and glass. However, its funding and research initiatives rather place an emphasis on developing local hydrogen markets by using hydrogen for heating and transportation. In the short term, the UK aims to develop “blue” hydrogen, which is perceived as cheaper, to replace household gas use. Funding for hydrogen innovation comes from the government, but revenue support is likely to be funded by levies on energy consumption. This approach seems unlikely to result in the green industrial leadership the government hopes to achieve. The unwillingness of the government to take strategic decisions on hydrogen types and uses means that its funding is stretched across different cases. And, while the UK participates in international standard-setting initiatives to better participate in global markets, it is not officially coordinating with or investing in hydrogen infrastructure that could connect it with Europe and thereby enable regional hydrogen trade. Given the rise in industrial policy measures including for hydrogen in the US and EU, the UK’s goal of becoming a major hydrogen player seems unlikely without a significant change in policy clarity and ambitio

Towards participatory cross-impact balance analysis: Leveraging morphological analysis for data collection in energy transition scenario workshops - Kurniawan, Jude; Apergi, Maria; Eicke, Laima; Goldthau, Andreas; Lazurko, Anita; Nordemann, Emily; Schuch, Esther; Sharma, Ajar; Siddhantakar, Natalya; Veit, Konstantin; Weko, Silvia (Energy Research & Social Science, 2022)
Keywords: Cross-impact balance analysis; Energy transition; Transdisciplinary research; Morphological analysis; Scenarios

Unlocking a Low-Carbon Future for Malaysia - Hermann, Judith; Apergi, Maria; Eicke, Laima; Goldthau, Andreas; Kurniawan, Jude; Schuch, Esther; Weko, Silvia (2022)

What determines local attitudes towards Jordan’s renewable energy transition? Evidence from household surveys - Weko, Silvia; Schuch, Esther (Climate Policy, 2024)
The potential for renewable energy to encourage sustainable development raises high hopes for the future among countries in the Global South. However, there has been less research on how energy transitions are perceived outside of the Global North and democratic contexts. This paper explores attitudes towards the energy transition in Jordan, where expert interviews reveal that a strong renewable energy industry has emerged from top-down government efforts to reduce energy dependency and costs. We perform an in-person household survey with 320 respondents in areas with different transition risks and benefits, and then test a series of hypotheses using regression analysis. In the four communities surveyed, income stress and climate concern influence attitudes, as well as perceptions of community benefits. National-level concerns also matter, including energy dependency and energy costs for all Jordanians. Our results highlight the importance of context: findings from the North are not universal and understanding transitions in the Global South requires studying them in their own right. Policy insights Jordanian policymakers should reverse their policy of blocking renewables to avoid public backlash. Jordanian policymakers and funders should promote projects in communities with high economic dependence on the fossil fuel industry to ensure local support in areas facing transition risks. Policymakers should highlight collective, not just individual benefits of transitions, as perceptions of community and country benefits increase support. Policymakers in highly energy-dependent countries like Jordan should frame renewables as an answer to local and national challenges such as high energy prices. Actors wishing to promote clean energy support in different contexts should investigate local dynamics to build communication strategies that frame transitions appropriately.
Created from Fastlane, Scopus look-up
Keywords: attitudes; climate concern; Energy transition; Jordan; public acceptance; renewable energy

Who believes in green growth? Strategic framing and technology leadership in the UNFCCC negotiations - Schmidt, Leonard; Apergi, Maria; Eicke, Laima; Weko, Silvia (Climate Policy, 2023)
Keywords: Framing; Green growth; Climate diplomacy; Environmental politics; International relations; UNFCCC